The effectiveness of deep learning in enhancing senior high school students’ critical thinking skills in physics learning - Nira Nurwulandari (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study aimed to analyze the effectiveness of the Deep Learning approach in improving senior high school students’ critical thinking skills in physics learning, particularly on dynamics material. This study used a pretest-posttest control group design and a quasi-experimental methodology. 64 students made up the sample, and they were divided into two groups: the experimental group and the control group. The experimental group was instructed using a Deep Learning approach consisting of the stages of understanding, applying, and reflecting, whereas the control group participated in conventional instructional activities. Research instruments included a critical thinking skills test covering analysis, evaluation, inference, and scientific reasoning, as well as an observation sheet of learning implementation. The findings revealed that the implementation of Deep Learning was classified as very high, achieving an average implementation percentage of 92%. Students in the experimental group showed greater improvement in critical thinking skills, as indicated by the increase in mean scores from 54.21 ± 7.35 to 82.47 ± 6.18, with an N-gain value of 0.61 categorized as moderate–high. In comparison, the control group obtained an N-gain value of 0.33, which fell into the moderate category. These results suggest that Deep Learning-based instruction was more effective than conventional teaching methods in improving students’ critical thinking skills and conceptual understanding in physics learning.